Community Satisfaction Analysis of the Implementation of Semen Gresik Rembang Factory’s CSR - Mahditia Paramita; Hendra Hendra (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2022)
Corporate Social Responsibility (CSR) is a form of corporate responsibility to the surrounding environment that the company must carry out to minimize environmental damage as a result of the establishment of the industry. This research wants to see the benefits of the program based on the results of community satisfaction assessment with quantitative and qualitative methods to determine the success of CSR program implementation. Public satisfaction with the implementation of the CSR program implemented by Semen Gresik Rembang Factory is directly proportional to the benefits obtained by the community. The success of the program is not only judged by the number of activities carried out, but also by the level of community satisfaction with the program and community participation in the program to support the improvement of the quality of human resources. Community capacity building is carried out through community empowerment programs to support sustainable development, which is an obligation in development in the world. The development and usefulness of activity programs need to be developed and expanded by beneficiaries to be able to solve problems that exist in the social, economic, and environmental spheres that are more effective and have a broader impact. The development and usefulness of activity programs need to be developed and expanded by beneficiaries to be able to solve problems that exist in the social, economic, and environmental spheres that are more effective and have a broader impact. The increase in community involvement also needs to be carried out not only in the process of identification, socialization, implementation, and monitoring of evaluation, but further participation until the community is able and participates in sharing more roles in the implementation of Corporate Social Responsibility activities carried out by Semen Gresik Rembang Factory.